Baseline-Free Damage Imaging for Structural Health Monitoring of Composite Lap Joint Using Ultrasonic-Guided Waves - Mohsen Barzegar; Dario J. Pasadas; Artur L. Ribeiro; Helena G. Ramos (IEEE Open Journal of Instrumentation and Measurement)
Damage imaging algorithms are crucial for evaluating the condition of critical structures such as adhesively bonded joints. Particularly during service, baseline-free structural health monitoring (SHM) is essential for robust and real-time evaluation. This article proposes and investigates the impact of the shape of the damage intensity distribution and damage index on the damage imaging of composite lap joints using a baseline-free SHM system. This system comprises a parallel array of piezoelectric transducers attached to both sides of the lap joint for generating and receiving ultrasonic-guided waves. Various features are extracted from the received signals to serve as damage indices, representing the peak amplitude and energy of the signals as well as the time of flight (ToF). Different shapes of damage intensity distribution, including elliptical, diamond, rectangular, and quadrilateral, are considered between pairs of sensors to investigate their effects on the total damage intensity distribution. To evaluate the impact of these parameters, a 2-D correlation coefficient was employed to compare the results obtained from the baseline-free SHM system with the image containing actual defects. The results reveal that the ToF was ineffective in providing high correlation and considering the signal’s energy with quadrilateral shape achieved the highest correlation.